Study of Adsorption-Desorption on Batik Industrial Dyes (Naphthol Blue Black) on Magnetite Modified Humic Acid (HA-Fe3O4) - Maya Rahmayanti; Erni Yunita; Nunung Faizah Yosi Putri (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The rapid development of the batik industry can pollute water resources and become an increasingly severe problem. This research studies the adsorption-desorption of naphthol blue-black (one of the dyes in batik liquid waste) by magnetite modified humic acid (HA-Fe3O4). The adsorption isotherm was studied using the Langmuir and Freundlich isotherm models. Meanwhile, desorption agents used in this study were distilled water and hydrochloric acid. The results show that the adsorption isotherm followed the Langmuir adsorption model with a maximum adsorption capacity of 2.41 mmol/g. Desorption studies show that the desorption efficiency of naphthol blue-black on HA-Fe3O4 is 0.058% and 5.86% in the desorption agent of distilled water and HCl (1 M)